Causal factors of low stakeholder engagement: a survey of expert opinions in the context of healthcare simulation projects. (June 2015) - Jahangirian, Mohsen; Borsci, Simone; Shah, Syed Ghulam Sarwar; Taylor, Simon J E
While simulation methods have proved to be very effective in identifying efficiency gains, low stakeholder engagement creates a significant limitation on the achievement of simulation modeling projects in practice. This study reports causal factors—at two hierarchical levels (i.e., primary and secondary)—that could significantly affect low stakeholder engagement in healthcare simulation projects. A self-completed questionnaire was administered online to 91 experts in the field from whom 37 responded. The results were reinforced using a bootstrapped sample ( n  = 1000). Data were analyzed using descriptive statistics, Kendal's tau-b correlations, and non-linear multiple regression. Based on our research, while such factors as "communication gap", "stakeholders' high workload", and "too much complexity involved" represent the most significant primary causal factors, some others such as "reluctance to change" proved interestingly insignificant. The research suggests that high-impact public health projects can exemplify the areas that will potentially generate engagement in the healthcare simulation domain.